2012
DOI: 10.5455/vetworld.2012.732-737
|View full text |Cite
|
Sign up to set email alerts
|

Real time RT-PCR assay for detection of different serotypes of FMDV in Egypt

Abstract: Aim: The present study indicated that rRT-PCR could be provided for the detection of FMDV in infected, contact and carrier cattle and also provide a rapid sensitive tool aiming to aid in rapid disease detection and control. Foot and Mouth disease virus serotypes O and A still existing in Egypt. In January 2012, sever outbreaks struck the animal population in most Egyptian 1 governorates. The causative virus was identified as FMDV SAT2. Material and Methods: Five samples of tongue epithelium (ET) and five oesop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Serotype O is the most endemic since 1970 (Samuel et al, 1990) while serotype A was isolated and identified in 2006 after importation of live animals from Ethiopia (Abed El-Rahman et al, 2006;El-Kholy et al, 2007;Knowles et al, 2007). The newest serotype is SAT-2, which was detected in 2012 (EL-Shehawy et al, 2012;Valdazo-González et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Serotype O is the most endemic since 1970 (Samuel et al, 1990) while serotype A was isolated and identified in 2006 after importation of live animals from Ethiopia (Abed El-Rahman et al, 2006;El-Kholy et al, 2007;Knowles et al, 2007). The newest serotype is SAT-2, which was detected in 2012 (EL-Shehawy et al, 2012;Valdazo-González et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Serotype O is the most endemic since 1970 (Samuel, et al, 1990) while serotype A was isolated and identified in 2006 after importation of live animals from Ethiopia (Abed El-Rahman, et al, 2006). The newest serotype is SAT-2, which was detected in 2012 (EL-Shehawy, et al, 2012;Valdazo-González, et al, 2012). The present work aims to evaluate the histopathological changes of the affected body organs in clinically infected died young and adult cattle and buffalos as well as isolate and identify the serotype of FMDV.…”
Section: Introductionmentioning
confidence: 99%
“…specificity and the ability to detect diverse FMDV strains (pan-reactivity) as an additional requirement over any routine FMD diagnostic assay [11]. In Nigeria, much attention is not given to FMD control and as a fall-out beef export contributes insignificantly to economic development as reflected by global distribution [2] due to trade exclusion from lucrative world markets [12].…”
Section: Introductionmentioning
confidence: 99%